Targeting the Microenvironment in Esophageal Cancer - Wang, Lei; Han, Huiqiong; Wang, Zehua; Shi, Litong; Yang, Mei; Qin, Yanru (Frontiers in Cell and Developmental Biology, 2021)
Esophageal cancer (EC) is the eighth most common type of cancer and the sixth leading cause of cancer-related deaths worldwide. At present, the clinical treatment for EC is based mainly on radical surgery, chemotherapy, and radiotherapy. However, due to the limited efficacy of conventional treatments and the serious adverse reactions, the outcome is still unsatisfactory (the 5-year survival rate for patients is less than 25%). Thus, it is extremely important and urgent to identify new therapeutic targets. The concept of tumor microenvironment (TME) has attracted increased attention since it was proposed. Recent studies have shown that TME is an important therapeutic target for EC. Microenvironment-targeting therapies such as immunotherapy and antiangiogenic therapy have played an indispensable role in prolonging survival and improving the prognosis of patients with EC. In addition, many new drugs and therapies that have been developed to target microenvironment may become treatment options in the future. We summarize the microenvironment of EC and the latest advances in microenvironment-targeting therapies in this review.